In vivo evaluation of [11C]preladenant positron emission tomography for quantification of adenosine A2A receptors in the rat brain. Issue 2 (February 2017) - Zhou, Xiaoyun; Khanapur, Shivashankar; de Jong, Johan R; Willemsen, Antoon TM; Dierckx, Rudi AJO; Elsinga, Philip H; de Vries, Erik FJ
[ 11 C]Preladenant was developed as a novel adenosine A2A receptor positron emission tomography radioligand. The present study aims to evaluate the suitability of [ 11 C]preladenant positron emission tomography for the quantification of striatal A2A receptor density and the assessment of striatal A2A receptor occupancy by KW-6002. Sixty- or ninety-minute dynamic positron emission tomography imaging was performed on rats. Tracer kinetics was quantified by the two-tissue compartment model, Logan graphical analysis and several reference tissue-based models. Test–retest reproducibility was assessed by repeated imaging on two consecutive days. Two-tissue compartment model and Logan plot estimated comparable distribution volume ( V T ) values of ∼10 in the A2A receptor-rich striatum and substantially lower values in all extra-striatal regions (∼1.5–2.5). The simplified reference tissue model with midbrain or occipital cortex as the reference region proved to be the best non-invasive model for quantification of A2A receptor, showing a striatal binding potential ( BP ND ) value of ∼5.5, and a test–retest variability of ∼5.5%. The brain metabolite analysis showed that at 60-min post injection, 17% of the radioactivity in the brain was due to radioactive metabolites. The ED 50 of KW-6002 in rat striatum for i.p. injection was 0.044–0.062 mg/kg. The study demonstrates that [ 11 C]preladenant is a suitable tracer to quantify striatal A2A receptor density and assess A2A receptor occupancy by A2A receptor-targeting molecules.